Development, modelling and characterization of metal micro-textured thermal interface materials - Kempers, Roger (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2010)
A metal micro-textured thermal interface material (MMT-TIM) has been developed to address the shortcomings of conventional TIMs. In the present study, the MMT-TEVIs consist of silver foils with raised, small-scale, hollow features. Upon compression between two solids, these features plastically deform, conforming to the asperities of the contacting surfaces thereby achieving intimate contact in the contact regions and a high conductivity bondline.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin